Pengaruh Efisiensi Pakan dan Waktu Pemuasaan Yang Berbeda Terhadap Pertumbuhan dan Kelangsungan Hidup Ikan Nila (Oreochromis niloticus) - Siegers, Willem Hendry; Prayitno, Yudi; ., Sudirman (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2021)
Fasting is one strategy to overcome the problem by giving the minimum possible amount of feed but the growth of the fish is not hampered. Fasting also means feed with a predetermined time interval in the hope that the fish can experience an increase in appetite after the fish are fasted. This study aims to determine the fisting effect of tilapia and feed efficiency et growth which fasting is the best to do. The research method used a simple completely randomized design with four treatments and two repetitions each, namely feed without fasting (treatment A), one day of fasting one day of feed (treatment B), one day fasting two days of feed (treatment C) and one day of fasting and three days of feed (treatment D). Fish were to eating three times a day at 08.00, 12.00, 17.00 at satiation. Fish seeds were given pellet feed as much as 3% of body weight. The results of analysis of variance test showed that fish feeding had no significant effect (P<0.05) at growth in weight and length and feed efficiency but significantly (P>0.05) at survival rate. The results showed that the best weight and length growth values in tilapia were found in treatment D with an average weight growth value of 12.20±0.22 gram, length 2.41±0.24 cm. The best feed efficiency was found in treatment B, which was 60.83±6.60% and the best survival was found in treatment A a with an average value of 86.67±0,00%.